Fabrication and analytical evaluation of three‐dimensional microsolenoids achieved in fused silica by femtosecond‐laser‐based microsolidifying process. (1st October 2013) - Liu, Keyin; Yang, Qing; Zhao, Yulong; Chen, Feng; Shan, Chao; Fan, Xiaole; Meng, Xiangwei; Du, Guangqing; Bian, Hao
Abstract : In this reported work, a femtosecond‐laser‐based microsolidifying method was employed to fabricate three‐dimensional (3D) microsolenoids by injecting liquid metal into helicalmicrochannels in fused silica and solidifying the liquid metal, and a proposed finite element method‐3D‐vector simulation approach was used to analyse the structure influence. An improved femtosecond laser irradiation followed by chemical etching technology was used to fabricate the complex 3D microchannels, in which an optimal laser power compensation strategy of tuning laser power from 7 to 12 mW was involved. Asilanisation process was carried out before the injection process to facilitate the injection of gallium. 3D numerical simulations of the microsolenoids were carried out by an electromagnetic‐coupled analysis method; and a simulation‐based co‐energy calculation method was used to evaluate the inductance of the 3D microsolenoids. 3D microsolenoids of optimised configurations were then achieved according to the analytical results.